Genetic Diversity for Stripe Rust Resistance in Wheat Landraces and Identification of Accessions with Resistance to Stem Rust and Stripe Rust. Issue 5 (1st September 2014) - Sthapit, Jinita; Newcomb, Maria; Bonman, J. Michael; Chen, Xianming; See, Deven R.
ABSTRACT: Stripe rust, caused by Puccinia striiformis f. sp. tritici, and stem rust, caused by P. graminis f. sp. tritici, are economically important diseases of wheat ( Triticum aestivum L.). Stripe rust continues to cause huge economic losses in major wheat‐growing regions as new races of the pathogen frequently emerge. Wheat landraces from diverse geographic regions are a potential source of novel rust resistance genes. In search of multiple rust resistance, a total of 652 landrace accessions from 54 countries previously screened for resistance to stem rust pathogen (race Ug99) were tested for resistance to current races of stripe rust in Pullman and Mt. Vernon, WA. Of the accessions, 165 showed resistance to stripe rust in the field, and 30 of them also had resistance to stem rust. The 652 landraces were genotyped with 72 simple sequence repeat markers, and 500 of them had data for 8633 single nucleotide polymorphism (SNP) markers covering the whole wheat genome. Genetic analysis based on SNP markers grouped the resistant landraces into nine different clusters in an unweighted pair group with arithmetic mean dendrogram and three groups in principal coordinates analyses, suggesting that resistant genotypes are genetically diverse and are expected to possess diverse resistance genes. Landraces with resistance to stem rust and stripe rust have both global and regional importance as sources of developing new and diverse resistant germplasm.